STRATEGI DAN OPTIMALISASI SUMBER DAYA DESA DALAM MENDORONG PERTUMBUHAN EKONOMI MANDIRI DAN INKLUSIF DI DESA SUKARAJA KECAMATAN WARUNGGUNUNG KABUPATEN LEBAK - Muara Torang Hadomuan; Yohanes Oci; Deni Permana; Nur Rizka Oktovia; Devi Triana (Ensiklopedia Research and Community Service Review, 2026)
Village development has a strategic role in supporting national economic growth through optimizing local potential. Sukaraja Village, Warunggunung District, Lebak Regency has various resources that have the potential to be developed, but their use is not optimal in improving the welfare of the community. This research aims to analyze the potential of village resources, formulate strategies for village governments and communities in optimizing resources, and examine these optimization efforts in encouraging independent and inclusive economic growth. This PKM aims to analyze strategies and optimize village resources in encouraging independent and inclusive economic growth in Sukaraja Village, Warunggunung District. Village development has a strategic role in national development because villages are the basis of community economic activities supported by the potential of natural resources, human resources, and social capital. However, the utilization of this potential in Sukaraja Village is still not optimal, which is characterized by limited human resource capacity, low market and capital access, and lack of synergy between stakeholders. The method used in this activity is a participatory, educational, and implementive approach through the Community Service (PkM) program. The implementation of activities is carried out in stages including preparation and mapping of partner needs, presentation of materials to strengthen the capacity of village apparatus, development of village information disclosure systems, empowerment of community participation, implementation assistance, and monitoring and evaluation. The results of the activity show that a participatory approach and continuous mentoring are able to increase the understanding of village officials related to transparent and accountable resource management, as well as encourage active community participation in village development. Keywords: village resources, independent economy, inclusive economy, community empowerment, transparency, PkM